2015
DOI: 10.1155/2015/954932
|View full text |Cite
|
Sign up to set email alerts
|

Blade Crack Detection of Centrifugal Fan Using Adaptive Stochastic Resonance

Abstract: Centrifugal fans are widely used in various industries as a kind of turbo machinery. Among the components of the centrifugal fan, the impeller is a key part because it is used to transform kinetic energy into pressure energy. Crack in impeller's blades is one of the serious hidden dangers. It is important to detect the cracks in the blades as early as possible. Based on blade vibration signals, this research applies an adaptive stochastic resonance (ASR) method to diagnose crack fault in centrifugal fan. The A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…The non-stationary signals are divided into a great many of small segments, and each small segment can be regarded as a stationary or cyclostationary signal. Therefore, the traditional spectrum analysis technology still has important research significance and a very wide range of applications in the rotating machinery fault diagnosis for its simplicity and intuitive [13][14][15]. The most representative spectral analysis technologies are holospectrum technology [16][17][18], full-spectrum technology [19] and vector spectrum technology [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…The non-stationary signals are divided into a great many of small segments, and each small segment can be regarded as a stationary or cyclostationary signal. Therefore, the traditional spectrum analysis technology still has important research significance and a very wide range of applications in the rotating machinery fault diagnosis for its simplicity and intuitive [13][14][15]. The most representative spectral analysis technologies are holospectrum technology [16][17][18], full-spectrum technology [19] and vector spectrum technology [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Qin et al, found the frequency range selection characteristic of re-scaling frequency stochastic resonance because of the driving frequency limitation of bistable stochastic resonance and then separated vibration components with different frequencies by iteratively using stochastic resonance [ 21 ]. Hu and Li applied an adaptive stochastic resonance method to diagnose crack defect [ 22 ]. However, there is seldom reference in the literature about the centrifugal compressor blade crack detection by using stochastic resonance methods.…”
Section: Introductionmentioning
confidence: 99%
“…In severe cases when rolling bearings early break down during serving the machines, the machines can be damaged. In fact, the unpredictable failures may cause serious damage to machinery and equipment, so the extraction of early defects is very important to ensure the reliable operation of the machinery [3]. It is difficult for the vibration signal of the rolling bearing which is nonstationary and strongly modulated to detect weak fault characteristics under strong background noise [4].…”
Section: Introductionmentioning
confidence: 99%